2021
DOI: 10.1002/ccr3.4202
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculated hepatic focal nodular hyperplasia: A case report and review of the literature

Abstract: Focal nodular hyperplasia (FNH) is a common asymptomatic benign hepatic tumor encountered in middle‐aged women. However, pedunculated FNH is exceedingly rare and more frequently associated with complications. That is why surgical management is mandatory in this form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…We experienced FNH in a child who was born following IVF, and we assume that there might be a correlation between IVF and FNH in a healthy child. Identical to the controversial effect of oral contraceptives on FNH, which is still not definite, more investigation is needed to find the possible connection between IVF and FNH [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We experienced FNH in a child who was born following IVF, and we assume that there might be a correlation between IVF and FNH in a healthy child. Identical to the controversial effect of oral contraceptives on FNH, which is still not definite, more investigation is needed to find the possible connection between IVF and FNH [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…(2021) [ 5 ] Male/5 RUQ pain 9 cm × 10 cm × 12 cm Seg 5, 8 Normal US, CT, and MRI Surgery No complications No Ismail et al . 2021 [ 10 ] Female/38 Asymptomatic 4.5 cm × 3.5 cm × 3 cm Seg 3 Normal N/A (detected intraoperatively during surgical repair of hernia) Surgery No recurrence Yes Akaguma et al . (2023) [ 20 ] Female/35 RUQ abdominal pain 7 cm × 7 cm × 5 cm Seg 6 N/A US and CT Surgery No complication Yes OCP oral contraceptives, N/A not answered, Seg segment, US ultrasonography, CT computed tomography, RUQ right upper quadrant, MRI magnetic resonance imaging, CEUS contrast enhanced ultrasound, EUS endoscopic ultrasound, CRP c-reactive protein, WBC white blood cell, AST aspartate aminotransferase, ALT alanine aminotransferase …”
Section: Discussionmentioning
confidence: 99%
“…To date, several authors have reported pedunculated cases of FNH, while most of them were associated with clinical symptoms that required intervention [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Recently, Akaguma et al [ 31 ] successfully performed laparoscopic surgery for pedunculated FNH in a female patient during pregnancy due to the increased risk of developing complications and severe clinical manifestations.…”
Section: Current Landscape Of Pedunculated Lesions In Fnhmentioning
confidence: 99%
“…The majority of FNH cases are asymptomatic and usually detected as incidental findings during physical and imaging examinations or surgical procedures. However, pedunculated FNH may sometimes present with acute abdominal pain, dyspepsia, epigastric discomfort, nausea, vomiting or a tender palpable abdominal mass [ 19 , 29 ]. In addition, alpha-fetoprotein (AFP) levels and liver function tests are generally within normal limits [ 10 , 85 ].…”
Section: Clinical Manifestations and Diagnostic Workupmentioning
confidence: 99%
See 1 more Smart Citation